BUSINESS ANALYSIS OF MUD CRAB (Scylla spp.) FISHING IN BANDENGAN WATERS KENDAL REGENCY - Hogantoro, Ega Heidar; Dewi, Dian Ayunita Nugraheni Nurmala; Hapsari, Trisnani Dwi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Kendal Regency is one of the areas in northern Central Java which has potential resources for mud crabs (Scylla spp.). Communities in Kendal Regency use folding traps and gill nets to catch mud crabs (Scylla spp.). The catching activities of mud crabs in Bandengan waters Kendal are carried out all the time, without providing a recovery period on the ecosystem cycle at the fishing location. This study aims to analyze the technical and financial feasibility of catching mud crabs using folding traps and gill nets. The method used in this research is descriptive method with a survey approach. Data collection methods used are direct observation, interviews, literature and documentation. The analytical method used is break even point analysis, R/C ratio, B/C ratio, and payback period. The results showed that folding traps and gill nets are feasible to run because folding traps have a BEP value of IDR 43,286 (<sale price); production BEP value of 333 kg/year (<production/year); value of R/C ratio 1.38 (> 1); the B/C ratio value is 0.38 (> 0); PP value for 1 year 7 months while gill net has a BEP value of IDR 41,480 (<sale price); production BEP value of 313 kg/year (<production/year); value of R/C ratio 1.45 (> 1); the B/C ratio value is 0.45 (> 0); PP value for 1 year 6 month. Gill nets is more feasible to run than folding traps because it has a higher R/C ratio and B/C ratio than folding traps. Then the BEP and PP values is lower if it as compared with folding traps.